Analisis Kesulitan Siswa Dalam Pembelajaran Sains: Studi Empirik Dalam Karya Ilmiah - John Rafafy Batlolona; Noke Kesaulya; Damaris Manuputty; Marike Muskitta (Jurnal Penelitian Pendidikan IPA, 2023)
This study discusses students' difficulties in learning science related to writing simple scientific papers. So far, teachers in the classroom have focused more on providing knowledge without involving a good understanding of concepts related to writing scientific papers. Therefore, the purpose of this research is to analyze the causes of students' difficulties in writing scientific papers. This research is a servei study in the form of 24 questions in the form of questionnaires for 148 people consisting of 57 male students and 91 female students in the Science class at SMA Negeri 14 Central Maluku. The findings prove that the dominance of language in research has become an obstacle in publication. This has made writing scientific papers difficult. Another aspect is the interference of different cultural views, linking the text with the views of the scientific community, arguments, grammar rules, and so on. All of this must be supported by a good understanding of scientific concepts by utilizing the original surrounding environment as a strength value that is different from other regions. This study then proposes suggestions for further research when students write for publication in a way to make claims to their knowledge. Future research is to focus on deeper investigation of ways to make knowledge claims and how students deal with that aspect so that the publication of scientific papers can be achieved.